Cultural disconformity and its influence on the relationship between personality traits and entrepreneurial intention among student youths of Saudi Arabia / Khloud Abdullah A. M. Mohammad - A. M. Mohammad, Khloud Abdullah (2019)
Saudi Arabia has a unique culture and society, which has influence on the way entrepreneurship is perceived and experienced. Research about entrepreneurs in the Middle East and North Africa Region (MENA) and particularly in Saudi Arabia is, however, still in its infancy. This study is among the first to explore entrepreneurship within the Kingdom of Saudi Arabia. The aim of the present research study is twofold. Firstly, it attempts to assess the appropriateness of using personality traits to explain entrepreneurial intention. Secondly, it explores the possible moderating role of Cultural Disconformity in affecting the relationship between traits and intention. To meet the objectives of the study, this research focuses on the youths of the Kingdom, represented by students of public and private universities. The research utilises the Traits theory and the National Culture theory, as well as the interplay between these two (2) theories to explain Entrepreneurial Intention. The research framework introduces Cultural Disconformity as the moderating variable in affecting the relationship of five (5) selected personality traits as the independent variables; Locus of Control, Innovativeness, Independence, Proactive-ness and Need for Achievement with the dependent variable Entrepreneurial Intention. The research was carried out involving 370 respondents from five (5) public universities in the kingdom. The results of this study found that youths in Saudi Arabia exhibit high intention to choose entrepreneurship as a career choice. The research finds significant relationship between three (3) independent variables; Proactive-ness, Innovativeness and Need for Achievement with Entrepreneurial Intention. The research, however, fails to establish similar relationships between Locus of Control and Independence with Entrepreneurial Intention. Additionally, the research also finds that Cultural Disconformity fails to moderate the relationships between the independent variables and the dependent variable. Despite the limitations of this research, the author provides a comprehensive list of recommendations and suggestions for future research but also give practical proposals to policy makers, universities leaders and other decisions makers, stakeholders in both public and private sectors in designing better policies to achieve the Saudi government’s Vision 2030 which aims to foster entrepreneurship in Saudi Arabia.